The Effect of Soil Texture and Irrigation on Rotylenchulus reniformis and Cotton - Moore, Scott R (Journal of nematology, 2013)
The reniform nematode, Rotylenchulus reniformis, is the most damaging nematode pathogen of cotton in Alabama. Soil texture is currently being explored as a basis for the development of economic thresholds and management zones within a field. Trials to determine the reproductive potential of R. reniformis as influenced by soil type were conducted in microplot and greenhouse settings during 2008 to 2010. Population density of R. reniformis was significantly influenced by soil texture and exhibited a general decrease with increasing median soil particle size (MSPS). As the MSPS of a soil increased from 0.04 mm in clay soil to > 0.30 mm in very fine sandy loam and sandy loam soils, R. reniformis numbers decreased. The R. reniformis population densities on all soil types were also greater with irrigation. Early season cotton development was significantly affected by increasing R. reniformis Pi, with plant shoot-weight-to-root-weight ratios increasing at low R. reniformis Pi and declining with increasing R. reniformis Pi. Plant height was increased by irrigation throughout the growing season. The results suggests that R. reniformis will reach higher population densities in soils with smaller MSPS; however, the reduction in yield or plant growth very well may be no greater than in a soil that is less preferential to the nematode